Mudharabah Compliance Analysis in Construction Service Companies: A Qualitative Case Study of CV Wafifudin Jaya, West Bandung Regency - Hadi Rahman; Sudana sudana (Institut Agama Islam Persis Bandung, 2025)
Mudharabah (profit-sharing partnership) is a foundational contract in Islamic commercial jurisprudence, yet empirical research examining its operationalisation in conventional Indonesian construction companies remains scarce. This study analyses the compliance of the profit-sharing arrangements practised by CV Wafifudin Jaya a construction and building-material service company in West Bandung Regency, West Java against the normative provisions of mudharabah in Islamic economics, with particular reference to DSN-MUI Fatwa No. 07/DSN-MUI/IV/2000. A qualitative single-case study design was employed, with primary data drawn from semi-structured interviews with the President Director, supplemented by document analysis and non-participant observation. Data were analysed using thematic analysis with a deductive framework derived from the rukn (pillars) and shurut (conditions) of mudharabah. The findings reveal that CV Wafifudin Jaya operates a flexible dual role mudharabah model: the company functions as shahibul maal (capital provider) in agricultural partnerships and as mudharib (fund manager) in construction sub-contracting arrangements. The scheme demonstrates substantive compliance with core mudharabah pillars contracting parties, capital provision, and profit-sharing but three compliance gaps are identified: the absence of written contracts, the lack of explicit loss-bearing clauses, and insufficient specification of business scope. The study contributes to the literature on mudharabah operationalisation in non-banking commercial enterprises and proposes a five-element reform pathway for achieving documented Sharia compliance.